Obstetrics outcomes of women with sickle cell disease in a tertiary institution in Ibadan – a 10-year review (2024)
Background: Pregnancy in sickle cell disease (SCD) patients is associated with increased risk of fetomaternal morbidity and mortality. With improvements in management, education, awareness, and nutrition, more patients with SCD are maximizing their reproductive potential. Objectives: This review examined the pattern of complications and obstetrics outcomes of patients with SCD in a tertiary health facility. Materials and Methods: A descriptive retrospective study of 106 pregnant SCD patients who delivered at the University College Hospital, Ibadan between 1st January 2008 and 31st December 2017. Information on their demographic, medical and obstetrics characteristics, complications and outcome were obtained from their case notes using a pre-designed proforma. Data were analyzed using SPSS version 23. Results: Of the 106 cases reviewed, 64 (60.38%) had sickle cell anaemia (haemoglobin SS), 39 (36.79%) had haemoglobin SC and 3 (2.83%) had haemoglobin CC. The mean maternal age was 29.6±4.7 years. Majority, 83(78.3%), booked for antenatal care at mean gestational age (GA) of 19.4±8.7 weeks while the mean GA at delivery was 39.0±1.73 weeks. Bone pain crisis (38.8%) was the commonest non-obstetrics complication with 63.2% occurring among the HBSS genotype. The common obstetrics complications were preterm contraction, intrauterine fetal death (IUFD), and preeclampsia (each occurring among 27.3%). Overall, there were 84.9% live births and the overall fetomaternal outcome was satisfactory in 38.7%. Conclusion: Sickle cell disease in pregnancy has remained associated with increased risk of bone pain crises as well as preterm contractions, IUFD and preeclampsia. A multidisciplinary team approach is essential in ensuring a positive pregnancy outcome.